2013
DOI: 10.1371/journal.pone.0053815
|View full text |Cite
|
Sign up to set email alerts
|

Localizing Non-Retinotopically Moving Objects

Abstract: How does the brain determine the position of moving objects? It turns out to be rather complex to answer this question when we realize that the brain has to solve the motion correspondence problem in two kinds of reference frames: Retinotopic and non-retinotopic ones. We show that visual objects are mislocalized along a non-retinotopic motion direction. Observers viewed two successive movie frames each consisting of an outlined square and two target elements inside the square. In the non-retinotopic condition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…To date, the postdictive effect has been observed in several sensory modalities, including visual [15][16][17][18][19], auditory [22] and tactile [20,21] perception. Moreover, several studies have reported postdictive integration of audio-visual [24,25] and tactile-visual [23,26] signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the postdictive effect has been observed in several sensory modalities, including visual [15][16][17][18][19], auditory [22] and tactile [20,21] perception. Moreover, several studies have reported postdictive integration of audio-visual [24,25] and tactile-visual [23,26] signals.…”
Section: Discussionmentioning
confidence: 99%
“…The retrospective effect of the information about a physically subsequent event on the psychological response to a current event is known as postdiction [15]. Previous studies have demonstrated postdictive modulation of the location [15,16], size [17], shape [18] and orientation [19] of visual objects. Similarly, the perceived positions of tactile (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…3, a first stage of processing groups motion information and extracts reference frames that are used to compute the attributes of the moving objects. The use of nonretinotopic, motion-based reference frames has been supported by several studies (Agaoglu et al, 2012;Boi et al, 2009;Hisakata, Terao, & Murakami, 2013;Kawabe, 2008;Nishida, Watanabe, Kuriki, & Tokimoto, 2007;Öğmen, Otto, & Herzog, 2006;Yamada & Kawabe, 2013). On the basis of our results, we can summarize the reference-frame rules as follows: First, individual motion vectors are grouped according to their similarities (law of common fate).…”
Section: Discussionmentioning
confidence: 52%
“…The RFMF theory differs from these approaches by putting perceptual-grouping operations as an essential component of reference-frame extraction; in this context, the nonlinearity in the antagonistic interactions in Experiment 3b can be explained as an effect of perceptual grouping. Moreover, most theories of vision, including the aforementioned approaches to motion perception, are based on retinotopic representations, although mounting evidence is showing that perception is highly nonretinotopic (Agaoglu et al, 2012;Boi et al, 2009;Hisakata et al, 2013;Kawabe, 2008;Nishida et al, 2007;Öğmen et al, 2006;Shimozaki, Eckstein, & Thomas, 1999;Yamada & Kawabe, 2013). Hence, a fundamental gap exists between retinotopic theories and the nonretinotopic percepts that these theories attempt to explain.…”
Section: Discussionmentioning
confidence: 99%
“…The Ternus-Pikler paradigm is an effective method used to examine whether phenomena are based on non-retinotopic processing in the absence of eye movements [13][14][15][16][17][18][19][20] . The Ternus-Pikler illusion is a visual illusion of apparent motion 21 and consists of two frames separated by a short or long blank (inter-stimulus interval [ISI]; Fig.…”
mentioning
confidence: 99%